Exploring the interdependence between self-organization and functional morphology in cellular systems - Mancinelli, Gloria; Galic, Milos (Journal of cell science, 2020)
All living matter is subject to continuous adaptation and functional optimization via natural selection. Consequentially, structures with close morphological resemblance repeatedly appear across the phylogenetic tree. How these designs emerge at the cellular level is not fully understood. Here, we explore core concepts of functional morphology and discuss its cause and consequences, with a specific focus on emerging properties of self-organizing systems as the potential driving force. We conclude with open questions and limitations that are present when studying shape–function interdependence in single cells and cellular ensembles.